Monitoring of River Morphological Change Using Remote Sensing and Hec-Ras in Lusi River, Indonesia - Wijaya, Diva Darma; Jazaul Ikhsan,; Nursetiawan, (International Journal of Integrated Engineering, 2024)
Changes in river flow have become a natural cycle of the river. The Lusi River has problems with meanders due to sediment transport, which is difficult to control. A combination of GIS with RS and HEC-RAS simulation was used to monitor river flow. The water monitoring method utilizes four water indices: NDWI, MNDWI, ANDWI, and SAVI, while the MPM-Toffaleti method is used for simulation. By combining the four methods, accuracy values of 0.68 to 0.92 and precision levels of 0.60 to 0.93 were obtained. MNDWI obtained quite high results compared to other indices. The results showed that the Lusi River experienced quite extreme flow changes. Two flow cuts occurred. Considerable erosion occurred from 2003 to 2013 with a total lost area of 0.1943 km2, while from 2013 to 2023, there was erosion of 0.1177 km2. The HEC-RAS simulation of the Lusi River experienced erosion of 60 to 70.4 percent of the length of the stream. Changes in the riverbed in 2013 were found to be -1.1 ± 2.03 m, and then in 2023, the range of changes in the riverbed was -2.69 ± 1.29 m. Based on the results of the index and simulation of the Lusi River experiencing erosion in the flow, the level of erosion has increased every period.